Impact of public subsidies on micro and small business development in Georgia - Skhirtladze, Sophiko; Abramishvili, Zurab; Barbakadze, Irakli; Papava, Giorgi (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
The study evaluates the government’s subsidy program for micro and small businesses in Georgia. Firms that submitted business ideas that scored over a predetermined cutoff level received investment subsidies from the program. To analyze the effect of public support on firm-level financial and economic results, we use a sharp discontinuity design applied to firm-level survey data of beneficiary and non-beneficiary enterprises. The survey data is complemented by administrative data collected by the implementing agency, Enterprise Georgia. We find a significant positive impact on participating firms’ investment in the program’s first year. We also find weak evidence of public subsidies crowding out private investments in subsequent years. The state support program appears to have not affected sales, employment, or access to additional finance for beneficiary firms, even in the program’s early stages. The results are robust to sensitivity analysis.